Rentabilidad y liquidez en tiempos de covid en la finca San Fernando de la ciudad de Pasaje. - Delgado Ugarte, Betty Alanis; Ortega Cabrera, Dennis Orlando (Machala : Universidad Técnica de Machala, 2023)
The main objective of this case analysis is to measure the variations that the San Fernando company dedicated to the cultivation and sale of bananas locally and internationally suffered within the framework of the recent pandemic caused by the SARS-COV-2 virus, specifically it was carried out the study of the periods 2019, 2020, 2021 and 2022 in order to demonstrate whether there were positive or negative variations in their levels of liquidity, profitability and optimization of resources before, during and after the health emergency. To achieve the stated objectives, different financial analysis tools were used, with regard to measuring the monetary and percentage variations of the financial statements during the aforementioned periods, horizontal and vertical analysis was used to verify whether the company's liquidity increase or decrease, the liquidity ratios were used and, finally, to demonstrate the profitability indices in conjunction with the optimization of the resources that the entity has, it was necessary to apply the DuPont analysis. In the field of exports, one of the biggest problems that can arise for a producer is the closure of markets and ports since sales volumes decrease, causing illiquidity. Finca San Fernando is a company that seeks continuous growth and development. , which is why knowing the positive or negative effects on liquidity, profitability and optimization of resources is of vital importance, how the company behaves in the face of market limitations allows for better decision making. During the development of the research, in order to demonstrate and fulfill the established objectives, it was necessary to analyze and apply numerical and percentage data, therefore, quantitative research was essential in this work, for the interpretation of the results. of the numerical part and, the information obtained in the interview applied to the accountant and owner of the company, the qualitative modality was essential. With the limitation of export quotas and intensification of controls, it would be logical that the company during the pandemic would have reduced its liquidity and profitability rates compared to previous years. Likewise, it would be expected that after leaving the health emergency, these rates would rise again. However, the opposite occurs, the company during the year 2020 and 2021 at the height of the coronavirus is where it presents higher levels of profitability and liquidity, in numerical data one of the reasons was due to the increase in sales, but, how could it be increase sales with the closure and limitation of export quotas? When interviewing the owner and accountant, it was indicated that the management was quick in terms of new health safety certifications, so they were able to get a place on the boats to transport the fruit. With the lifting of restrictions, competitiveness increased, so their income was negatively affected.
El presente análisis de caso tiene por objetivo principal medir las variaciones que la empresa San Fernando dedicada al cultivo y venta de banano a nivel local e internacional sufrió en el marco de la reciente pandemia ocasionada por el virus SARS-COV-2, específicamente se realizó el estudio de los periodos 2019, 2020, 2021 y 2022 con la finalidad de evidenciar si se presentaron variaciones positivas o negativas en sus niveles de liquidez, rentabilidad y optimización de los recursos antes, durante y después de la emergencia sanitaria. Para el cumplimiento de los objetivos planteados se utilizó diferentes herramientas de análisis financiero, en lo que respecta a medir las variaciones monetarias y porcentuales de los estados financieros durante los periodos mencionados se utilizó el análisis horizontal y vertical, para verificar si la liquidez de la empresa aumento o disminuyo se utilizó los ratios de liquidez y, finalmente para evidenciar los índices de rentabilidad en conjunto con la optimización de los recursos que posee la entidad fue necesario aplicar el análisis DuPont. En el campo de las exportaciones uno de los mayores problemas que se le puede presentar a un productor es el cierre de mercados y puertos puesto que, los volúmenes de venta disminuyen provocando iliquidez, Finca San Fernando es una empresa que busca el crecimiento y desarrollo continuo, razón por la cual conocer los efectos positivos o negativos en la liquidez, rentabilidad y optimización de recursos es de vital importancia, el cómo se comporta la empresa ante limitaciones del mercado permite una mejor toma de decisiones. Durante el desarrollo de la investigación, con el fin de evidenciar y dar cumplimiento a los objetivos establecidos fue necesario del análisis y aplicación de datos números y porcentuales por lo que, la investigación cuantitativa fue esencial en el presente trabajo, para la interpretación de los resultados de la parte numérica y, la información obtenida en la entrevista aplicada al contador y propietario de la empresa la modalidad cualitativa fue indispensable. Con la limitación de cupos de exportación e intensificación de controles lo lógico sería que la empresa durante la pandemia hubiese reducido sus índices de liquidez y rentabilidad en comparación con años anterior, así mismo se esperaría que tras dejar la emergencia sanitaria dichos índices volviesen a subir, sin embargo ocurre lo contario, la empresa durante el año 2020 y 2021 en pleno auge del coronavirus es donde presenta mayores niveles de rentabilidad y liquidez, en datos números una de las razones fue por el aumento de las ventas, pero, ¿Cómo se pudo aumentar las ventas con el cierre y limitación de cupos de exportación? Al entrevistar al propietario y contador se indicó que la gestión fue rápida en cuanto a nuevas certificaciones de seguridad sanitaria se refiere, por lo que pudieron conseguir un lugar en las embarcaciones para transportar la fruta. Con el levantamiento de las restricciones la competitividad aumento por lo que sus ingresos se vieron afectados negativamente.
Keywords: ANALISIS FINANCIERO; ANALISIS HORIZONTAL; RENTABILIDAD; LIQUIDEZ